QIZQAPAN: A ROCK-CUT TOMB FROM THE MEDIAN, ACHAEMENID, SELEUCID OR PARTHIAN PERIOD?. (December 2021) - Rezaei, Iraj
Abstract : More than eight decades have passed since Edmonds's introduction to the rock-cut Tomb of Qizqapan, yet there are still ambiguities and questions regarding a number of aspects, specifically its dating. Different dates from the Median, Achaemenid, Seleucid, and Parthian periods have been proposed for this monument. However, out of all the proposed eras, none has been fully accepted by the majority of archaeologists, and disagreements regarding the date still continue. This article reviews and analyses previous proposals and discusses and evaluates other elements which affect the dating of this monument. The results show that by taking into account several factors, the most probable date for this tomb is the fourth century B.C., contemporaneous with the late Achaemenid and the early Seleucid period. The conclusion is that Qizqapan does have a Median identity but not a Median period date.